2017
DOI: 10.18632/oncotarget.16964
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC inhibitor valproate induces a bivalent status of the CD20 promoter in CLL patients suggesting distinct epigenetic regulation of CD20 expression in CLLin vivo

Abstract: Treatment with anti-CD20 antibodies is only moderately efficient in chronic lymphocytic leukemia (CLL), a feature which has been explained by the inherently low CD20 expression in CLL. It has been shown that CD20 is epigenetically regulated and that histone deacetylase inhibitors (HDACis) can increase CD20 expression in vitro in CLL. To assess whether HDACis can upregulate CD20 also in vivo in CLL, the HDACi valproate was given to three del13q/NOTCH1wt CLL patients and CD20 levels were analysed (the PREVAIL st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…79 In contrast, the analysis of three CLL patients from the PREVAIL study showed no CD20 induction upon pretreatment with valproic acid. 80 A plausible explanation might be that valproic acid induces a bivalent MS4A1 promoter status in primary CLL cells in vivo as it induces histone acetylation, but also transient recruitment of the transcriptional repressor EZH2 to the MS4A1 promoter (Figure 2, Table 1). Administering a DNMT inhibitor and pan-HDAC inhibitor (valproic acid, romidepsin, trichostatin A, SAHA) stimulates CD20 expression and might improve anti-CD20 therapy in vivo, at least in some patients with B-NHL.…”
Section: Regulation Of Cd20 Transcription and Its "Therapeutic Modulation"mentioning
confidence: 99%
“…79 In contrast, the analysis of three CLL patients from the PREVAIL study showed no CD20 induction upon pretreatment with valproic acid. 80 A plausible explanation might be that valproic acid induces a bivalent MS4A1 promoter status in primary CLL cells in vivo as it induces histone acetylation, but also transient recruitment of the transcriptional repressor EZH2 to the MS4A1 promoter (Figure 2, Table 1). Administering a DNMT inhibitor and pan-HDAC inhibitor (valproic acid, romidepsin, trichostatin A, SAHA) stimulates CD20 expression and might improve anti-CD20 therapy in vivo, at least in some patients with B-NHL.…”
Section: Regulation Of Cd20 Transcription and Its "Therapeutic Modulation"mentioning
confidence: 99%
“…There were cases of CD20-deficient lymphoma relapses identified following treatment with Rituximab-associated regimens in DLBCL 6 . Rituximab-induced downregulation of CD20 expression is mainly due to deacetylation of histones by histone deacetylases (HDACs) [9][10][11] , internalization of CD20 molecule 12 and loss of CD20/Rituximab complex from cell surface 13 . Insufficient surface CD20 protein affects Rituximabinduced lipid raft domain organization and downstream signalling, leading to Rituximab resistance 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The enhancer regions of MS4A1 (CD20) in DLBCL cells are H3K27ac 18 . Upregulation of CD20 expression by either specific inhibitors for HDAC6 (Tubacin and Ricolinostat) or non-specific HDAC inhibitors (Valproic acid and Romidepsin) showed sensitizing potential in Rituximab-induced cell death in malignant B cells [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Several studies have also begun to explore the therapeutic potential of HDAC inhibitors for CLL treatment. 13,14 However, the roles of individual HDACs in CLL biology have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%